Lithium battery recycling management and policy - Rahman, Mohammed Ataur; Rafia, Afroz (Inderscience, 2016)
Recycling of used lithium batteries has primarily focused on extracting active metal cobalt (Co) and lithium (Li). The price of cobalt is higher than the price of others metals. The price of Co and Li has increased due to production of electric and hybrid car. The used Li battery is the source of Li and Co and the optimal way of extract these metals from this waste are important. Hydrometallurgical method is used to recover Co and Li in laboratory scale with 48.8 Wh battery. Calcination on Co, Li and Cu extraction at 700°C was performed to remove organic compounds. Material after calcination was leached in different concentration of HCl and H2SO4 without and with hydrogen peroxide (H2O2) reducing agent. Experiment was conducted on recycling of 48.8 Wh battery and found that the recycling cathode 41 wt% and 8.5 wt% of the cell cathode and anode, which are 48.8% and 23.4% of the cathode and anode cell material price, respectively.